2020
DOI: 10.3906/biy-1912-83
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-specific protease 7 downregulation suppresses breast cancer in vitro

Abstract: Because breast cancer is complicated at the pathological, histological, clinical, and molecular levels, identification of new genetic targets against carcinogenic pathways is required to generate clinically relevant treatment options. In the current study, ubiquitin-specific protease 7 (USP7), which regulates various cellular pathways including Mdm2, p53, and NF–κB, was selected as a potential gene editing strategy for breast cancer in vitro. Anticancer activity of USP7 gene suppression has been evaluated thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…In addition, our data demonstrate a pivotal role of Usp7 for viability and competitive growth of breast cancer cells (Figures 4 and 6 ). In line with our data, the DUB Usp7, also known as Herpesvirus associated protease (HAUSP), is generally known to act tumor-promoting in various cancers 67 - 69 , 80 , including breast cancer 70 - 73 . Based on our results, we confirmed the tumor-promoting function of Usp7 in breast cancer.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In addition, our data demonstrate a pivotal role of Usp7 for viability and competitive growth of breast cancer cells (Figures 4 and 6 ). In line with our data, the DUB Usp7, also known as Herpesvirus associated protease (HAUSP), is generally known to act tumor-promoting in various cancers 67 - 69 , 80 , including breast cancer 70 - 73 . Based on our results, we confirmed the tumor-promoting function of Usp7 in breast cancer.…”
Section: Discussionsupporting
confidence: 87%
“…For all 12 hits, knockdown of the respective proteases by at least one of the two tested miR-E constructs sensitized murine PyB6-TA breast cancer cells to PI3K inhibition by BKM (Supplementary Figure S2 ). Finally, we decided to further investigate Usp7, Metap1 and Metap2 due to most distinct effects in the first validation assays and literature postulating tumor-promoting functions of these proteases 62 - 73 . Metap1 and 2 (isoforms) are metalloproteases that co-translationally remove the initiator methionine from newly synthesized proteins 74 , 75 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many DUBs are linked to cancer (34,35,46). For example, Usp7 is known to act as tumorpromoting in various cancer entities (47-50) including breast cancer (51)(52)(53). Together with the known cancer-promoting function of the UPS, the detection of many proteasomal components and DUBs as strong depletion hits proves the validity of our screening approach.…”
Section: Discussionmentioning
confidence: 85%
“…FT827/671 inhibited tumors by degrading the oncogenic E3 ligase MDM2 ( Turnbull et al, 2017 ). In the latest study, P5091 inhibitors showed robust tumor suppression effects in preclinical models of various tumors ( An et al, 2017 ; Wang et al, 2017 ; Hayal et al, 2020 ; He et al, 2020 ; Lee et al, 2020 ). Among these cancers, in colorectal cancer, P5091 improves the antitumor immune response and reduces the proportion of Tregs in tumor xenografts in mice ( Fu et al, 2019 ).…”
Section: Research On Dub Inhibitors and Their Effects On Srss And Taimmentioning
confidence: 99%